Bank loan supply during crises: The importance of geographic diversication - Sebastian Dörr; Philipp Schaz (University of Zurich, Department of Economics, 2019)
We classify a large sample of banks according to the geographic diversification of their international syndicated loan portfolio. Our results show that diversified banks maintain higher loan supply during banking crises in borrower countries. The positive loan supply effects lead to higher investment and employment growth for firms. Diversified banks are stabilizing due to their ability to raise additional funding during times of distress, which also shields connected markets from spillovers. Further distinguishing banks by nationality reveals a pecking order: diversified domestic banks are the most stable source of funding, while foreign banks with little diversification are the most fickle. Our findings suggest that the decline in financial integration since the recent crisis increases countries' vulnerability to local shocks.
Older version: https://www.econstor.eu/handle/10419/192897
Keywords: F30; G01; G15; G21; G32; 330; Diversification; Global Banking; Financial Stability; Syndicated Loan Market; Banking Crisis